Музыка – душа моя (жизнь и творчество русского композитора М.И. Глинки) - Novikov K. K. (Winter school marathon, 2017)
the article is devoted to the life and creative work of a famous Russian composer - Mikhail Ivanovich Glinka. His versatile personality is really striking. A great composer was also a great pianist, a chamber singer, a vocal tutor and even a writer. His interests besides music are amazing and diverse: he could speak several foreign languages, went in for zoology, botany, art and geography.He is the author of world-known operas "Ruslan and Lyudmila" and "Ivan Susanin" and many other orchestral works. He is by right the creator of the national classical music school.
Keywords: народная песня; композитор; composer; symphonic music; musical heritage; Russian historic opera; traditional national song; симфоническая музыка; музыкальное наследие; русская историческая опера